ACTIVITY OF Annona Squamosa PEELS EXTRACTS AGAINST TWO PATHOGENIC BACTERIA AND TWO BLOOD CANCER CELL LINES - & et al., Altaee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This research project was designed to assess the antibacterial and antitcancer activity by using the crude extracts of fresh and dried peels of Annona squamosa fruit. The fresh and dried peels were extracted by using three solvents, inculded (water, ethanol, and methanol) at different concentrations (stock, 50, 25, 12.5, 6.25) µg/ml. The antibacterial activity was estimated against Gram-positive bacteria (Staphylococcus aureus) and Gram - negative bacteria (Pseudomonas aeruginosa) using agar well-diffusion method. Results showed the appearance of different regions of inhibition. Antibacterial activity of alcoholic solvent extracts of the dry and fresh peels showed noticeable inhibitory activity against both tested bacteria when comparing the last one with the aqueous extract of peels. The results of anticancer activity estimation against two hematological blood cancer cell lines showed that the three solvents for fresh and dried peels caused a remarkable inhibitory effects and the ethanolic extracts of dried peels was the best. This encourage for the possibility of using peels extracts of Annona. squamosa as a natural resources for growth inhibiting of different types of bacteria and cancer cells.